2023
DOI: 10.3389/fnut.2023.1113099
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides as a risk factor for cognitive impairment: Natural substances are expected to become alternative measures to prevent and improve cognitive impairment

Abstract: Pesticides are the most effective way to control diseases, insects, weeds, and fungi. The central nervous system (CNS) is damaged by pesticide residues in various ways. By consulting relevant databases, the systemic relationships between the possible mechanisms of pesticides damage to the CNS causing cognitive impairment and related learning and memory pathways networks, as well as the structure–activity relationships between some natural substances (such as polyphenols and vitamins) and the improvement were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…Malathion exposure has the potential to disrupt this delicate balance, possibly escalating the aberrant changes associated with tauopathies such as AD. [ 155 ] In another experimental study by Moyano et al showed that exposure to the CP at a dose of 30 μM boosted GSK‐3β expression and activity in septal SN56 basal forebrain cholinergic neurons. This elevated GSK‐3β activity resulted in an increase in the phosphorylation of the tau protein.…”
Section: Effect Of Opps On Glial Cellsmentioning
confidence: 99%
“…Malathion exposure has the potential to disrupt this delicate balance, possibly escalating the aberrant changes associated with tauopathies such as AD. [ 155 ] In another experimental study by Moyano et al showed that exposure to the CP at a dose of 30 μM boosted GSK‐3β expression and activity in septal SN56 basal forebrain cholinergic neurons. This elevated GSK‐3β activity resulted in an increase in the phosphorylation of the tau protein.…”
Section: Effect Of Opps On Glial Cellsmentioning
confidence: 99%
“…Insecticides, including organophosphates and pyrethroids, act by binding to specific receptors in the central nervous system, primarily acetylcholinesterase . According to recent studies, prolonged exposure to these chemicals can disrupt normal levels of monoamines. This may increase the risk of neurological and developmental disorders. , …”
Section: Introductionmentioning
confidence: 99%
“…In above 65 years aged population is 11.7% and 10.8% of patients between 45-64 years of age [3]. Environmental pollutants i.e., pesticides are one of the risk factors for the development of cognitive impairment [4]. Current experimental evidence also revealed that the herbicide also causes cognitive dysfunction in rats via synaptic impairment and hippocampal neuron damage [5].…”
Section: Introductionmentioning
confidence: 99%